2021
DOI: 10.1002/jnr.24927
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of early oligomeric α‐synuclein pathology and its impact on the dopaminergic system in the (Thy‐1)‐h[A30P]α‐syn transgenic mouse model

Abstract: The histopathological hallmark of the Parkinson's disease (PD) brain is the presence of Lewy bodies (LBs) and Lewy neurites (LNs), intraneuronal lipid-and protein-rich complexes mainly consisting of fibrillar alpha-synuclein (α-syn) (Spillantini et al., 1997). Misfolding of native α-syn causes dynamic changes in its conformation, leading to formation of oligomers followed by protofibrillar species and finally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Another study successfully detected αSYN oligomers in transgenic mice (Thy1-h-αSYN*A30P) with αSYN-PLA similar to those employed in the present study. Of note, no signal was observed in the non-transgenic control mice [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study successfully detected αSYN oligomers in transgenic mice (Thy1-h-αSYN*A30P) with αSYN-PLA similar to those employed in the present study. Of note, no signal was observed in the non-transgenic control mice [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that dopamine is involved in novelty processing and can enhance hippocampal synaptic plasticity [47] , [48] , [49] , [50] , spreading of α-syn pathology throughout regions interconnected with dopaminergic areas most likely contributes to abnormalities in dopamine-dependent neuromodulation of cognitive processes. However, as we previously found that the levels of dopamine or its metabolites are unchanged in Thy-1-h[A30P] α-syn tg mice [51] , such an effect may possibly instead be the result of a harmful interaction between α-syn and either dopamine itself or its receptors.…”
Section: Discussionmentioning
confidence: 75%
“…It has particular relevance when it comes to exploring post-mortem tissue surfaces. In some cases, the liability and heterogenicity of early aggregates limit the use of traditional immunohistochemistry with conformational antibodies ( Behere et al, 2021 ). Others might claim that antigen preservation is not the issue but rather the limited knowledge of the conformers in the tissue.…”
Section: Immuno-labelling Reporting Of α-Syn Aggregationmentioning
confidence: 99%
“…Over the past few years, AS-PLA became a popular tool to study what authors usually termed early α-syn oligomers. It has been applied to study oligomer distribution in the midbrain of young mice ( Behere et al, 2021 ) or the brain samples of MSA and PD patients ( Sekiya et al, 2019 ). Bengoa-Vergniory and colleagues used AS-PLA in several models and situations to evaluate the presence of oligomers upon treatment with the molecular tweezer CLR01: PD patients' brain extracts, human dopaminergic cultures over-expressing α-syn, and human α-syn-overexpressing mouse model tissue ( Bengoa-Vergniory et al, 2020 ).…”
Section: Immuno-labelling Reporting Of α-Syn Aggregationmentioning
confidence: 99%